Export Promotion: what works? - Marcelo Olarreaga; Stephan Sperlich; Virginie Trachsel (Fondation pour les études et recherches sur le développement international (FERDI), 2017)
We explore the heterogeneity in returns to export promotion across countries using a semi-parametric varying coefficient model. We find that a one percent increase in export promotion budgets generates an increase in export growth between 0.03 and 0.08 percent. Returns in terms of GDP per capita show less heterogeneity and vary from 0.05 to 0.07. Differences in the characteristics of export promotion agencies drive the heterogeneity in returns to export promotion across countries. More importantly, characteristics that may help export growth are not necessarily those that help GDP per capita growth.
Keywords: F13; C14; 330; Impact evaluation; export promotion